Fabrication and Analysis of Ion-Engineered ZnO Device Structures for Optoelectronic Applications - Fareeha Younus; Ahmed Shuja; Muhammad Ali (IEEE Photonics Journal, 2023)
ZnO-based devices are highly promising for applications involving light-matter interaction. This work explores the impact of light-matter interaction on ion-induced ZnO structures and their respective energy band profiles. Incorporation of various ions, (Au+, B+, Cu+, P+) into the ZnO lattice, deposited via magnetron sputtering on an n-type Si substrate was investigated in detail. To assess the impact of these ions on the ZnO surface, monte-carlo simulations at low energies were performed and optimal ion dose and energy conditions were determined. The resulting post-fabrication devices underwent comprehensive structural, morphological, optical, and electrical diagnostics. X-ray diffraction (XRD) analysis confirmed the well-maintained crystal structure of the ZnO lattice along the <100> direction for all implant sequences. Notably, the gold (Au+) implant exhibited the highest light extinction into the ZnO matrix, as indicated by the extinction coefficient and refractive index data. This observation suggested that Au+ implantation could effectively generate electron-hole pairs. The photovoltage and dark/light current measurements provided further evidence of enhanced light-matter interactions and responsivity in the Au+-implanted devices owing to light-induced currents. Furthermore, the energy bands of all implant cases were profiled by Charge Deep Level Transient Spectroscopy (Q-DLTS) measurements by evaluating discrete energy states within the ZnO lattice.